Public Relations Role of @debrads.id on Instagram in Promoting the Victoria Run 2023 Event by deBrads Race Management - Siahaan, Tunggul; Muharman, Deddy (LSPR Institute of Communication & Business, 2025)
This study delves into the strategies and effectiveness of social media promotion for event engagement, specifically examining deBrads’ promotional campaign for the Victoria Run 2023 held in Jakarta. Utilizing Instagram as the primary promotional platform, the analysis reveals how early promotion, clear and concise messaging, and strategic use of interactive content foster engagement with the target audience. The campaign highlighted essential tactics such as creating anticipation through timely announcements, providing incentives like discounts, and optimizing language for relatability and emotional connection. By aligning these efforts with established public relations practices, deBrads successfully boosted brand awareness, increased participant registration, and cultivated an engaged community around the event. The findings contextualize these practices within existing literature on digital promotion and social media marketing, affirming Instagram's role as a powerful tool for event promotion in the digital age. The study concludes with recommendations for future campaigns, emphasizing consistent, interactive, and audience-focused content to enhance engagement and build lasting brand visibility